2006
DOI: 10.1080/08860220500530841
|View full text |Cite
|
Sign up to set email alerts
|

Simple Renal Cyst Prevalence in Internal Medicine Department and Concomitant Diseases

Abstract: A total of 684 patients who had not been diagnosed with renal cyst but had undergone abdominal ultrasonography for various reasons were evaluated. Patients with and without renal cyst were classified into two groups and were compared in terms of hypertension (HT), hyperlipidemia (HL), diabetes mellitus (DM) and obesity (body mass index: > or = 30 kg/m2) prevalence. Although 94 patients (13.7%) were established with a renal cyst, 590 patients (86.3%) did not have a renal cyst. The mean age of the patients estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
4
16
3
Order By: Relevance
“…Our study extends the findings of a relationship between simple renal cysts and hypertension shown in previous cross-sectional and casecontrol studies [7,8,15].…”
Section: Discussionsupporting
confidence: 83%
“…Our study extends the findings of a relationship between simple renal cysts and hypertension shown in previous cross-sectional and casecontrol studies [7,8,15].…”
Section: Discussionsupporting
confidence: 83%
“…Subcentimeter masses were not considered in our analysis because incidental masses smaller than 1 cm can generally be ignored [10,17]. The prevalence in our study was similar to that in previous reports, particularly when subcentimeter masses were excluded [6,18].…”
Section: Discussionsupporting
confidence: 82%
“…Two case-control studies found no significant differences between SRC patients and controls 4, 18 . Cross-sectional studies on healthy subjects and internal medicine outpatients indicated that serum uric acid level were associated with SRC development upon univariate analysis 14, 15 , and, indeed, even upon multivariate analysis adjusted for confounders including age, sex, eGFR, and renal stones 17 . Blijderveen et al .…”
Section: Discussionmentioning
confidence: 95%
“…Some authors found that diabetes was not significantly associated with SRC development 8, 14, 18 . Others reported significant increases in the prevalence of diabetes (9.7–24.1%) in patients with SRC, but this was not significant upon multivariate modeling 1, 12, 15, 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation